POTASSIUM FERTILIZATION IN HYBRID FORAGE Sorghum GROWN IN DIFFERENT SOIL MANAGEMENT SYSTEMS IN EASTERN AMAZON - Galvao, Jessivaldo Rodrigues; Fernandes, Antonio Rodrigues; Alves Siva, Vicente Filho; Pinheiro, Daniel Pereira [UNESP]; Melo, Nilvan Carvalho [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
Sorghum is grown in areas and environmental situations very dry and/or too hot, where productivity of other cereals is uneconomical. Aiming to evaluate the production of three sorghum hybrids, because of potassium and management systems, grown in Oxisol with low productive capacity, an experiment was conducted in the field, in the area of the Federal Rural University of Amazonia/UFRA, Belem campus The experimental design was randomized in blocks, arranged in a factorial 4 x 3 x 2 with four replications. The factors were: four doses of potassium (50, 100, 200 and 300 kg ha(-1)) as KCl, three sorghum hybrids (Qualimax, Volumax and AG 2005-E) and two tillage systems (no-till and conventional). The tillage produced a higher shoot dry weight of sorghum, and the hybrid and Volumax and Qualimax had incomes above the AG2005-E. The contents of the elements N, P, K, Ca and Mg in the leaves of sorghum grown with tillage were higher than those found in conventional tillage. Doses of potassium resulted in greater increase in MSPA tillage using 40% less potash fertilizer with the conventional system.
Keywords: Sorghum bicolor L.; Nutrients tillage; Silage